A Comparative Study of National Identity Dimensions in Educational System of Canada, France, Japan and Iran - Ferdows Khojasteh; Alireza Assareh; Abrahim Hajiani; Alireza Araghieh (Comparative Education Society of Iran ( CESIR), 2020)
The aim of study is to identify different dimensions of national identity in education system policies of selected countries based on Herbert Mead's theory. The present study is a qualitative, non-experimental and comparative study using George Bereday's four-step approach. The unit of observation is at macro level (countries) and sample selection strategy is "different systems, different outcomes" including Canada, France, Iran and Japan. The data collection method is documentary (upstream documents of selected countries), books and articles. For data analysis, content analysis method was used. The findings of study reveal that in Japan's centralized education system and after the Meiji Revolution, emphasis was placed on fundamental Japanese philosophy and Confucian values. In France's centralized education system, the emphasis is on training based on republican values ​​(equality, democracy, individual and social rights and responsibilities), and in Canada - despite federal parliamentary democracy - there is no unified educational institution. In the centralized educational system of Iran, importance is given to Islamic philosophy and values. Although the past is emphasized in Iran, Japan, and France, Canada cares more about past achievements (such as the construction of railroads) than historical events.  The benefit of experiences of Canada, France and Japan- in terms of the dimensions of national identity- can pave the way for policies in Iran's education system.